IMPLEMENTASI PROGRAM DESA SEHAT UNTUK MENINGKATKAN KESEHJATERAAN MASYARAKAT SEBAGAI PERWUJUDAN SDGS DESA - Fiqriyah Hanum; Isna Fitria Agustina (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study examines the implementation of the Desa Sehat (Healthy Village) Program as a manifestation of the Sustainable Development Goals (SDGs) at the village level, focusing on Larangan Village, Candi District, Sidoarjo Regency. The Desa Sehat Program serves as a strategy to improve community welfare through basic health services, empowerment, and enhanced citizen participation. The study employs a descriptive qualitative approach with purposive sampling and data analysis using the Miles and Huberman model. The findings reveal that the program has been implemented fairly well, achieving an indicator score of 77.34%, including zero infant mortality and successful handling of drug abuse cases. However, challenges remain in expanding BPJS Health coverage, addressing unmet health service needs, and improving maternal health facilities. The analysis based on Edward III’s implementation theory indicates that communication, resources, implementer disposition, and bureaucratic structure play crucial roles in the program’s effectiveness. The policy implications highlight the need for local governments to strengthen cross-sector coordination, enhance human resource capacity, and utilize digital technology for health program monitoring. Furthermore, increasing community participation through health cadres and community-based education is recommended as a strategic effort to accelerate the achievement of the Desa Sehat and Sejahtera (Healthy and Prosperous Village) goals in alignment with the SDGs framework